1987
DOI: 10.1192/bjp.150.4.533
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of the Performing and Recording of Physical Examinations by Psychiatric Trainees

Abstract: The physical examination on admission, as recorded in the psychiatric case notes, was assessed for 100 consecutive admissions under the age of 65. Assessment was made on the presence or absence of reference to 43 items of examination and the recording of the examinations was found to be uniformly poor. One of the authors re-examined 50 patients within 48 h of admission and the findings were then compared with the initial recorded examination. Significant unrecorded positive findings were most frequent in the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
24
0

Year Published

1992
1992
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 5 publications
1
24
0
Order By: Relevance
“…Studies that have evaluated this aspect of care have concluded that most psychiatric patients do not receive a thorough PE (Hodgson & Adeyemo, 2004;Murray & Baillon, 2013;Rigby & Oswald, 1986;Vanezis & Manns, 2010). Various reasons have been suggested for this shortcoming including:…”
Section: Introductionmentioning
confidence: 99%
“…Studies that have evaluated this aspect of care have concluded that most psychiatric patients do not receive a thorough PE (Hodgson & Adeyemo, 2004;Murray & Baillon, 2013;Rigby & Oswald, 1986;Vanezis & Manns, 2010). Various reasons have been suggested for this shortcoming including:…”
Section: Introductionmentioning
confidence: 99%
“…On the one hand, the psychiatrist is often ideally placed to screen for and manage physical problems; indeed, the psychiatrist may be the only point of contact with health services for some patients. On the other hand, without further training or experience, psychiatrists may not necessarily provide the best care for patients (Rigby & Oswald, 1987), and care might be better delegated to other health care professionals with an appropriate medical background -in particular, the primary care health team (National Institute for Clinical Excellence, 2002;Welthagen et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Current evidence suggests that this opportunity is rarely grasped. Physical examinations by psychiatric trainees are usually done badly (Rigby & Oswald, 1987); when patients are admitted less than 75% are examined at all, and there is rarely any attempt to take a physical history (Osborn & Warner, 1998).…”
Section: Discussionmentioning
confidence: 99%